1994
DOI: 10.1161/01.cir.90.4.1638
|View full text |Cite
|
Sign up to set email alerts
|

Safety observations from the pilot phase of the randomized r-Hirudin for Improvement of Thrombolysis (HIT-III) study. A study of the Arbeitsgemeinschaft Leitender Kardiologischer Krankenhausärzte (ALKK)

Abstract: Background Adjunctive therapy for thrombolysis in acute myocardial infarction consists of platelet inhibition with aspirin and thrombin inhibition with heparin. Thrombin inhibition may be improved by the use of hirudin as indicated by experimental and phase II clinical studies. The randomized, double-blind phase III r-Hirudin for Improvement of Thrombolysis study (HIT III) compared a recombinant hirudin (HBW 023) with heparin. The primary end point was the incidence of death or reinfarction.Methods and Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0
5

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(76 citation statements)
references
References 15 publications
0
71
0
5
Order By: Relevance
“…Com validade questionável em função de um elevado crossover (36%) para o grupo de tratamento intravenoso, não houve demonstração de benefício em desfechos clinicamente relevantes com aumento das taxas de reinfarto. Em três estudos clínicos subsequentes, a HNF em administração venosa associada ao uso de fibrinolítico aumentou as taxas de sangramento maior [197][198][199] No estudo CREATE 201 , pacientes com IAMCST com 12 horas do início dos sintomas foram randomizados para reviparina ou placebo e analisados de forma duplo-cega. A reviparina estava associada a uma redução de 13% no objetivo primário composto de óbito/infarto recorrente/AVC em relação ao placebo.…”
Section: -Heparina Não Fracionada (Hnf)unclassified
See 1 more Smart Citation
“…Com validade questionável em função de um elevado crossover (36%) para o grupo de tratamento intravenoso, não houve demonstração de benefício em desfechos clinicamente relevantes com aumento das taxas de reinfarto. Em três estudos clínicos subsequentes, a HNF em administração venosa associada ao uso de fibrinolítico aumentou as taxas de sangramento maior [197][198][199] No estudo CREATE 201 , pacientes com IAMCST com 12 horas do início dos sintomas foram randomizados para reviparina ou placebo e analisados de forma duplo-cega. A reviparina estava associada a uma redução de 13% no objetivo primário composto de óbito/infarto recorrente/AVC em relação ao placebo.…”
Section: -Heparina Não Fracionada (Hnf)unclassified
“…Com validade questionável em função de um elevado crossover (36%) para o grupo de tratamento intravenoso, não houve demonstração de benefício em desfechos clinicamente relevantes com aumento das taxas de reinfarto. Em três estudos clínicos subsequentes, a HNF em administração venosa associada ao uso de fibrinolítico aumentou as taxas de sangramento maior [197][198][199] . Estudos observacionais já sugeriam doses menores como estratégia eficaz na obtenção de maior segurança, ajustadas ao peso do paciente (bolus de 60 UI/Kg até 4.000 UI com infusão contínua subsequente de 12 UI/Kg/h até 1.000 UI, com o objetivo de se obter um TTPa entre 50-70 segundos).…”
unclassified
“…The Thrombolysis in Myocardial Infarction (TIMI)-9A and Hirudin for Improvement of Thrombolysis (HIT)-III trials only enrolled patients with acute myocardial infarction, 30,31 whereas the Global Use of Strategies to Open Occluded Coronary Arteries (GUSTO)-2A trial also included patients with unstable angina and those with myocardial infarction who were ineligible for thrombolytic therapy. 32 The doses of hirudin given in the TIMI-9A and GUSTO-2A studies, which are illustrated in Table 3, were higher than that used in the OASIS-2 trial.…”
Section: Adjunct To Thrombolytic Therapymentioning
confidence: 99%
“…When used at a slightly higher dose, hirudin was more effective than heparin. Based on the results of the HIT-III trial, 31 however, it is unlikely that this medium-dose hirudin regimen would be safe in conjunction with thrombolytic agents.…”
Section: Adjunct To Thrombolytic Therapymentioning
confidence: 99%
“…Results from clinical trials with hirudin, a highly specific thrombin inhibitor, have shown that the therapeutic window for thrombin inhibitors may be narrower than expected (4)(5)(6). Furthermore, thrombin inhibitors will not by themselves prevent the continuing conversion of prothrombin, the most abundant of the vitamin K-dependent clotting proteins in the blood stream, to thrombin as long as the activity of factor Xa in the prothrombinase complex is uninhibited.…”
mentioning
confidence: 99%